The non-sulfated ulvanobiuronic acid of ulvans is the smallest active unit able to induce an oxidative burst in dicot cells. (15th October 2021) - Paulert, Roberta; Brunel, Fabrice; Melcher, Rebecca L.J.; Cord-Landwehr, Stefan; Niehues, Anna; Mormann, Michael; Moerschbacher, Bruno M.
Abstract: Ulvans from green algae are promising compounds for plant protection because they are environmentally friendly and induce plant defense responses. We analyzed the structure-function relationship of ulvan polymers and oligomers for their elicitor activity in suspension-cultured cells of three dicot species. The polysaccharide from Ulva fasciata was characterized regarding its monosaccharide composition, degree of sulfation, and molecular mass. The polymer was partially depolymerized using acid hydrolysis, and the oligomers were separated using size exclusion chromatography. The oligomeric fractions were analyzed revealing mostly sulfated and de-sulfated ulvan dimers. Both the polymer and the oligomer fractions induced an NADPH oxidase-dependent oxidative burst in plant cells. The elicitor activity of the ulvan dimers did not require sulfation. By identifying the smallest elicitor-active unit, HexA-Rha, we took an important next step to understand how the structure influences ulvan elicitor responses. The desulfated ulvan dimer is discussed as a promising agro-biologic for sustainable agriculture. Highlights: Ulvan polymers and oligomers elicit an oxidative burst in different dicot cells. Ulvan dimers consisting of a uronic acid and rhamnose are the smallest elicitor-active fragments. Sulfation is not required for elicitor activity of the dimers.